Strategi Optimasi Proses dan Peningkatan Daya Saing Pada UMKM Burger Lubuk Begalung - Boby Sugara Lubis; Farhan Handica; Rizky Muslim; Vini Khumaira; Desi Permata Sari (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The fast-food industry is growing rapidly amid changing consumer consumption patterns. Products like burgers are popular due to their practicality and adaptability. However, MSMEs face competitive challenges, such as Bao Burger in Padang City. Key issues include conventional marketing strategies and limited employee training. This study aims to support Bao Burger through digital marketing strategies and employee development. Results indicate a 50% increase in social media followers, a 30% rise in sales volume, and a 12.5% improvement in customer satisfaction. Digital strategies effectively expand market reach and enhance customer experiences. Recommendations are provided for other MSMEs to adopt digital technologies to strengthen their competitiveness.